ANALISIS KELAYAKAN PENGEMBANGAN USAHA RUMAH MAKAN MBOK SEMAH MEGALUH – JOMBANG - Deni Widyo Prasetyo; Erik Bisri Alamsyah (Yos Soedarso Economic Journal (YEJ), 2020)
Rumah Makan Mbok Semah has a plan to develop a business in the food sector. Rumah Makan Mbok Semah has a problem about whether its business development plan can provide feasibility for the company's future development. The purpose of this study was to determine the feasibility of a food business development plan with research limitations on the assessment of market and financial aspects. The objects in the interviews and questionnaires are business owners and residents around the place of business. Data on the market aspect is analyzed using the Strengths, Weaknesses, Opportunities, Threats (SWOT) method and the financial aspects using the Net Present Value (NPV) Method, the Internal Rate of Return (IRR) Method and the Payback Period (PBP) Method. The results of the research on the Market Aspect show that the Mbok Semah Restaurant has Strengths, Weaknesses, Opportunities and Threats that have been analyzed and the risk impact is well anticipated. In the Financial Aspect, the results of the Net Present Value (NPV) Method show that cash funds that have been collected from year to year if assessed at their current state with a positive value at the end of year 5 of IDR 29,577,421, -, Internal Rate of Return (IRR) ) shows the ability of the company's efforts to provide an annual average return / dividend of 20.494% and the Payback Period (PBP) method shows the company's ability to return all investment costs is 4 years and 8 months. Based on the results of the financial analysis, it shows that all the eligibility criteria have been financially fulfilled, so that business development is feasible to be carried out under normal conditions.Keywords: Business Feasibility; PBP; NPV; IRR; SWOT